Total synthesis of (+/-)-petasitolone and (+/-)-fukinone - Pasikanti, Srinivas; Reddy, D. Srinivasa; Iqbal, Javed; Dubey, Pramod Kumar; Das, Parthasarathi (Synthesis-Stuttgart, 2009)
An efficient, general, and fully stereocontrolled synthesis of eremophilane-type compounds is disclosed. The approach features a highly diastereoselective Diels-Alder/aldol sequence to give a common intermediate, which is subsequently exploited to produce (+/-)-petasitolone and (+/-)-fukinone in a short sequence.

Efficient synthesis of varenicline - Pasikanti, Srinivas; Reddy, D. Srinivasa; Venkatesham, B.; Dubey, P. K.; Iqbal, Javed; Das, Parthasarathi (Tetrahedron Letters, 2010)
Synthesis of varenicline the antismoking drug has been achieved in six steps with 10% overall yield. A Diels-Alder reaction, oxidative cleavage of an olefin and reductive amination remain as key steps in the synthesis (C) 2009 Elsevier Ltd. All rights reserved.